Molecular Cloning and expression of carbohydrate binding module (CBM40) from Vibrio cholerae Non O1 neuraminidase in E. coli - Nadiawati, Alias; Asmad, Kari; Shadariah, Mamat (2017)
A gene encoding CBM40 domain was screened from five bacteria samples which were Pseudomonas aeruginosa (ATCC 27853), Bacillus cereus (ATCC 14579), Staphylococcus aureus (ATCC 33862), Salmonella thypii (ATCC 14028) and Vibrio cholerae Non-O1. All the DNA samples were subjected for PCR amplification and resulted only Vibrio cholerae Non-O1 showed an amplified PCR product at 530 bp with 177 amino acid lengths. Sequence analysis through NCBI database has showed 99% similarity with Vibrio cholerae neuraminidase, NanH (M83562). The confirmed CBM40 gene was further ligated into pET 22b(+) and transformed into E. coli BL21(DE3) host by heat shock method. The putative cloned construct was further verified by sequencing service. The CBM40 gene was expressed insolubly in pellet after induced with 1mM IPTG at 18˚C (post-induction) for 24 hours. Maximum expression was observed at 20 hours after post-induction time. For purification strategy, pellet was lysed in a resuspension buffer containing (8 mM Na2HPO4, 286 mM NaCl, 1.4 mM KH2PO4, 2.6 mM KCl and 1% SDS (w/v) at pH 7.4) for 30 minutes at room temperature and proceed to sonication. The filtered supernatant was undergo nickel affinity chromatography with different concentrations imidazole of 10, 50 and 100 mM. The fraction was subjected to 10 kDa cut-off concentrator followed by SDS PAGE method and coomassie blue staining. The purified protein was stored at -80°C prior to use for the next protein assay and biochemical characterizations.